Thoracic approaches in atrial septal defect closure a comparative study - Gupta, Manju; Mishra, Pankaj Kumar; Bathla, Amit; Shoeb, Mohd; Prasad, Jagdish (International Surgery Journal, 2017)
Background: Atrial septal defects (ASD) are one of the most common cardiac malformations. Being asymptomatic, diagnosis is not always made in childhood and may be delayed to adolescence or adulthood. The incidence of ASD in female is twice that of male, so greater emphasis has been placed on the cosmetic results of the operation. Methods: In this study, we retrospectively compare results 100 patients of ASD closure through a right anterolateral thoracotomy incision and median sternotomy incision. Between August 2011 to August 2016, out of total 100 patients with ostium secundum ASD, 50 patients operated by right anterolateral thoracotomy have mean age 16.74 yrs, mean weight 28.77 kg, mean Height 122.06 cm and 50 patients with midline sternotomy have mean age 17.07 year, mean weight 29.24 kg, mean height 122.20cm. Results: There was no mortality in both groups. Per operatively mean operating time, mean CPB time, mean cross clamp time in thoracotomy was 130.08±8.16min, 48.68±5.10min, 29.70±4.21 min while in sternotomy was 121.34±8.30 min, 45.62±4.10 min, 28.28±2.82 min respectively. When compared, there is significant increased duration in operating and CPB time in thoracotomy while cross clamp time was non-significant. Mean duration of ICU and Hospital stay in thoracotomy group was 1.78±0.58days and 6.74±1.77 days when compared to sternotomy group in which it was 2.40±0.495 days and 7.66±1.40 days which is significantly less when compared. Postoperatively and in follow up thoracotomy group have better cosmesis when compared. Conclusions: Surgical treatment of osteum secondum ASD using right anterolateral thoracotomy approach has low operative risk better cosmetic results and patient satisfaction.